The Effect of Consumer Trust on the Growth of Online Payment Platforms: A Case Study of PayPal and Stripe - Sen, Sunanda (Shodh Sagar Journal of Commerce and Economics, 2024)
An examination of the influence that consumer trust has on the expansion and success of online payment platforms, with a particular emphasis on PayPal and Stripe, two of the most prominent companies in the industry. As the number of digital transactions continues to increase on a global scale, consumer trust has emerged as an essential component in the success of online payment services in terms of acceptance and continued use. An examination of the relationship between trust and consumer behavior, platform expansion, and market penetration is presented through a comparative case study of PayPal and Stripe. In order to gain an understanding of the impact that key characteristics like security, privacy, transparency, and user experience play in establishing and sustaining consumer trust, these crucial components are evaluated. quantifiable information, such as the number of users and the volume of transactions, as well as qualitative insights gleaned from consumer feedback and the characteristics of the platform. According to the findings, trust is a significant factor in determining user loyalty and platform expansion. Businesses that place a higher priority on security and transparency beat their rivals in this regard. useful information for companies and payment platforms that are looking to increase the level of trust that customers have in them and to propel growth in the digital economy.